Interaction between a complex fluid flow and a rotating cylinder - Cuong Mai Bui; Thinh Xuan Ho (Vietnam Journal of Science, Technology and Engineering, 2022)
The flow of a thixotropic Bingham material past a rotating cylinder is studied under a wide range of Reynolds and Bingham numbers, thixotropic parameters, and rotational speeds. A microstructure transition of the material involving breakdown and recovery processes is modeled using a kinetic equation, and the BinghamPapanastasiou model is employed to represent shear stress-strain rate relations. Results show that the material’s structural state at equilibrium depends greatly on the rotational speed and the thixotropic parameters. A layer around the cylinder resembling a Newtonian fluid is observed, in which the microstructure is almost completely broken, the yield stress is negligibly small, and the apparent viscosity approximates that of the Newtonian fluid. The thickness of this Newtonian-like layer varies with the rotational speed and the Reynolds number, but more significantly with the former than with the latter. In addition, the lift and moment coefficients increase with the rotational speed. These values are found to be close to those of the Newtonian fluid as well as of an equivalent non-thixotropic Bingham fluid. Many other aspects of the flow such as the flow pattern, the unyielded zones, and strain rate distribution are presented and discussed.